Conditional depletion of mast cells has no impact on the severity of experimental epidermolysis bullosa acquisita. Issue 5 (12th March 2015) - Kasprick, Anika; Yu, Xinhua; Scholten, Julia; Hartmann, Karin; Pas, Hendri H.; Zillikens, Detlef; Ludwig, Ralf J.; Petersen, Frank
<x xml:space="preserve">Abstract</x> The role of mast cells (MCs) in autoimmunity is the matter of an intensive scientific debate. Based on observations in different MC‐deficient mouse strains, MCs are considered as fundamental players in autoimmune diseases. However, most recent data suggest that the outcome of such diseases is strongly affected by the individual mouse strain used. By the use of two c‐Kit mutant MC‐deficient mouse strains and one c‐Kit‐independent strain, we here investigated the role of MCs in a systemic Ab transfer model of epidermolysis bullosa acquisita, a subepidermal autoimmune blistering skin disease characterized by autoantibodies against type VII collagen. While C57BL/6J‐KitW‐sh/W‐sh mice developed an unexpected increased blistering phenotype, no significant differences to WT controls were seen in WBB6F1‐KitW/W‐v or the novel Mcpt5‐Cre iDTR animals. Interestingly, in a local Ab transfer model, which induces a localized disease, we showed that application of high concentrations of anti‐COL7 (where COL7 is type VII collagen) Abs induced MC activation and MC‐dependent edema formation that did, however, not contribute to blister induction. Our results indicate that in the autoimmune disorder epidermolysis bullosa acquisita MCs do not contribute to the immune‐mediated tissue injury. Modern c‐Kit mutant‐independent MC‐deficient mouse strains will help to further redefine the role of MCs in autoimmunity.